FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT DELAY (STUDI PADA PERUSAHAAN MANUFAKTUR DI BEI) - Rosalina, Rizky Yuniar; Kurnia, Kurnia (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is meant to examine the influence of firm size, profitability, and audit opinion, Public Accountant Firm (PAF) reputation, audit tenure and the complexity of company operation to the audit delay. The population is all manufacturing companies which are listed in Indonesia Stock Exchange. Firm size is proxied by total assets, profitability is measured by return on assets, audit opinion is measured by reasonable opinion without exception and reasonable opinion with the exception, PAF reputation is measured by the size of Big Four PAF and Non Big Four PAF, audit tenure is measured by frequently change PAF and not change PAF, the complexity of the company operations is measured by having a subsidiary and not having subsidiary, and audit delay is measured by the late and timeliness. The samples are manufacturing companies which are listed in Indonesia Stock Exchange (IDX) in 2013-2015 periods and have been selected by using purposive sampling, and 48 companies have been selected as samples. The analysis method has been done by using multiple linear regression model. The result of the research shows that the firm size, profitability, audit opinion, PAF reputation, audit tenure and the complexity of company operation give significant influence to the audit delay.Keywords: profitability, audit opinion, PAF reputation, complexity of the company operation, audit delay.